Processo(s) de destituição do poder familiar que envolvem mulheres em situação de rua e seus bebês: uma análise psicossocial - Assoni, Giseli de Fátima (2022)
Scientific literature and the experience of psychology in the courts of law show that homeless women are separated from their children in the maternity ward and lose family power in actions of dismissal. In this way, this research aimed to analyze judicial processes of removal of family power that involve homeless women and their babies to understand the meanings present in the discourses about these women in these lawsuits, which support the removal of family power or deny it. In order to do so, processes from 2019 and 2020 were selected, from which a general analysis of the most recurrent aspects of these actions was carried out and, later, two cases were chosen for an analysis with the meaning cores, based on the socio-historical theory. As a result, it can be pointed out that the dismissal of these women happens as a rule, in addition, the meaning cores point out that they are described as an a-historical being, having their street condition given as natural. As well, the meanings that lead to a dehumanization of women are frequent, placing them as a being without affection for theis baby, a drug user – condition not understood as a health issue -, who does not want to take care of theis child, who has no home - disregarding the housing problem in Brazil. Finally, it is important to highlight the standardizing character of motherhood imposed by the various professionals who participate in the evaluation process, and the imposition of a universalization of the "conditions" necessary for the realization of the role of mother, which is in disagreement with the current legislation in Brazil